PROTOTYPE ANTENA OMNIDIRECTIONAL MIKROSTRIP PATCH ARRAY SEBAGAI PENGUAT TRANSMITTER RADAR PESAWAT TERBANG PADA FREKUENSI 1030MHZ - Arif Fahmi; Dodi Setiabudi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Radar SSR (Secondary Surveillance Radar) is an equipment to detect and determine the position and target data around him actively, where the plane took active if it receives the RF signal emitted secondary radar. In this study aims (1) to design a prototype omnidirectional microstrip patches array for applications Radar SSR (Secondary Surveillance Radar) according to the characteristics of the antenna by using the software High Frequency Structure Simulator version 13 (HFSS v13) that operate at a frequency of 1030-1090 MHz and get characteristics of the antenna such as Voltage Standing Wave Ratio (VSWR), the radiation pattern and gain (2) Implement the design of antenna omnidirectional microstrip patches array into physical form and measure VSWR, gain and radiation pattern characteristics of the prototype has been created and analyzed the characteristics Between desaian antenna with the prototype antenna that has been made. This research method using the rectangular microstrip patches dimensional array to determine the size of the microstrip antenna array patches and simulated using HFSS v13 software. The results of the analysis parameters pacth microstrip antenna array in HFSS v13 Software demonstrate the value of Ref. AMPL his 40.950739 dB, the analysis results pacth microstrip antenna array using the software HFSS v13 obtained gain value by achieving -29dB, and the results of the analysis, the value of the radiation pattern reaches the radiation pattern of 33.28dBm. Keywords: SSR, HFSS v13, VSWR, gain, radiation pattern, antenna, microstrip pacth array.